SENGKETA TANAH MANDIKU: STUDI KASUS TUNTUTAN MASYARAKAT ATAS HAK MILIK TANAH DI KECAMATAN TEMPUREJO KABUPATEN JEMBER, 2007-2010 (MANDIKU LAND DISPUTES: A CASE STUDY OF DEMANDS UPON THE PROPERTY RIGHTS OF LAND IN THE DISTRICT OF JEMBER REGENCY TEMPUREJO, 2 - Munawaroh, Siti; Burhan, Edy; Sasmita, Nurhadi (Publika Budaya, 2014)
Demands of the farmers in the village Mandigu Sidodadi and Rural Pondokrejo become one of the cases that arise in the reform era, starting with the installation of the boundaries a by Perhutani and the claim of Perhutani that the land occupied by the Residents Pondokrejo and Mandigu were owned by Perhutani. The farmers had the notion that the land has a meaning as an economic resource. Through Struggle Farmers, the farmers of Mandigu Sidodadi and Pondokrejo tried to fight for their land rights claimed by Perum Perhutani. It employed a qualitative approach with interviews and documentation as data collection efforts, and take the subject of social and political movements performed by Farmers Struggle. This study describes the socio-political movements performed by Struggle Farmers. With a focus on three main issues, namely land status, demands of the Struggle Farmers and Resistance Action conducted from 2007 to 2010. The conclusion is that the demand of the farmers was no longer result exploitative relations but also because of the openness of the system that provides opportunities for farming from to launch the movement. Keywords: land conflicts, political and social movements, demands of farmers, Farmers Struggle. ABSTRAK Tuntutan petani di Mandiku Desa Sidodadi dan Desa Pondokrejo menjadi salah satu kasus yang muncul di era reformasi. diawali dengan masalah pemasangan patok batas yang dilakukan Perhutani dan Pengakuan Perhutani bahwa tanah yang ditempati oleh Warga Mandiku dan Warga Pondokrejo merupakan kawasan Hutan yang dimiliki Perhutani. Petani memiliki anggapan bahwa tanah memiliki arti sebagai sumber ekonomi petani. Melalui wadah Petani Perjuangan, para petani di Mandiku Desa Sidodadi dan Desa Pondokrejo berusaha memperjuangkan hak atas tanah mereka yang telah diakui oleh Perum Perhutani. Melalui pendekatan kualitatif dengan wawancara dan dokumentasi sebagai upaya pengumpulan data, serta mengambil subyek gerakan sosial politik yang dilakukan oleh Petani Perjuangan. Penelitian ini mendeskripsikan gerakan sosial politik yang dilakukan oleh Perjuangan Petani. Dengan fokus pada tiga permasalahan utama yaitu Status tanah, Tuntutan Petani Perjuangan dan Aksi Perlawanan dilakukan dalam batasan tahun 2007 hingga 2010. Kesimpulan yang dapat diperoleh, Tuntutan Petani bukan lagi diakibatkan hubungan ekploitatif tapi juga karena adanya keterbukaan sistem yang memberikan peluang kepada petani untuk melakukan pergerakan. Kata kunci: konflik tanah, gerakan sosial politik, Tuntutan petani, Perjuangan Petani.